2014
DOI: 10.5380/rcc.v6i1.33455
|View full text |Cite
|
Sign up to set email alerts
|

Análise Histórica Dos Resultados Do Exame De Suficiência Do Conselho Federal De Contabilidade

Abstract: A reprodução dos artigos, total ou parcial, pode ser feita desde que citada a fonte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
4
0
9
Order By: Relevance
“…In Brazil, the Bar Exam is offered three times a year for the undergraduate or law student, in the last year or in the last two semesters of the undergraduate course. In the case of Accounting, the study by Bugarim et al (10) analyzed the performance of participants in the issues of National Licensure Exam and found a decrease in approval levels, from 83.52% in its first edition in 2000 to 23.78% passing in 2012. In 20 exam editions, the average pass rate was 18%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, the Bar Exam is offered three times a year for the undergraduate or law student, in the last year or in the last two semesters of the undergraduate course. In the case of Accounting, the study by Bugarim et al (10) analyzed the performance of participants in the issues of National Licensure Exam and found a decrease in approval levels, from 83.52% in its first edition in 2000 to 23.78% passing in 2012. In 20 exam editions, the average pass rate was 18%.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be more positive perception about the exam and its impact on the development and growth of the profession than actually reducing accounting courses in the country. By analyzing the answers of 220 accountants, we found that 81.82% believe that the exam provides professional appreciation and 82.73% realize that the exam helps select the most qualified professionals, although 53.61% believe that the exam system needs to be improved, in particular to suit the realities of the accountant (10)(11)16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O teste é composto de 40 questões, sendo 10 questões pertencentes à área denominada de "Formação Geral", que é comum a todos os cursos e busca avaliar o conhecimento e a competência do aluno em assuntos de conhecimento geral; e mais 30 questões pertencentes à área denominada de "Formação Específica" (PAIVA; ROSA, 2016, p. 99 (BUGARIM et al, 2014). Esta resolução considera que: [...] o objetivo do exame de suficiência implica no atendimento de um nível mínimo de conhecimentos necessários ao desempenho das atribuições deferidas ao Contabilista, além de se revestir da função de fiscalização do exercício profissional, em caráter preventivo (OLIVEIRA NETO; KUROTORI, 2009, p. 10).…”
Section: Critérios E Regulamentação Da Avaliação Dos Cursos Superioreunclassified
“…A (8) . Na seara marasmática de lideranças legislativas diplomadas na categoria de enfermagem, surge, da microrregião de Ilhéus-Itabuna, um representante de uma histórica família de barões do cacau, o paladino para conduzir os destinos da qualificação profissional do enfermeiro: Lúcio Quadros Vieira Lima, o remidor.…”
unclassified